What do we mean when we say “democracy”’?: learning towards a common future through popular higher education - Amsler, Sarah (PM Press, 2017)
This chapter explores how a small project in popular higher education presents both opportunities and challenges for learning new democratic subjectivities and social relationships that challenge neoliberal forms. It draws on my experiences as a member of an autonomous co-operative for free, co-operative, higher education in a small city in England called the Social Science Centre. The chapter is organized around a question raised by a fellow member of the Centre: ‘what do we mean when we say “democracy”?’ I will explain both the importance and impossibility of answering this question, and consider how it opens up new understandings of the political and pedagogical conditions of radical informal learning spaces. I then consider what, if anything, is radical about this particular space, and how abandoning ‘the radical’ may heighten our receptivity to it. Finally, the chapter considers the role that non-community-based spaces of popular higher education can play in the proliferation of critical thinking, capacities for ‘commoning’ and the creation of democratic publics in contexts where individualism and class division presently prevail.